Association between discordant immunological response to highly active anti‐retroviral therapy, regulatory T cell percentage, immune cell activation and very low‐level viraemia in HIV‐infected patients. (June 2014) - Saison, J.; Ferry, T.; Demaret, J.; Maucort Boulch, D; Venet, F.; Perpoint, T.; Ader, F.; Icard, V.; Chidiac, C.; Monneret, G.; ,
Summary The mechanisms sustaining the absence of complete immune recovery in HIV‐infected patients upon long‐term effective highly active anti‐retroviral therapy (HAART) remain elusive. Immune activation, regulatory T cells (Tregs) or very low‐level viraemia (VLLV) have been alternatively suspected, but rarely investigated simultaneously. We performed a cross‐sectional study in HIV‐infected aviraemic subjects (mean duration of HAART: 12 years) to concomitantly assess parameters associated independently with inadequate immunological response. Patients were classified as complete immunological responders (cIR, n = 48) and inadequate immunological responders (iIR, n = 39), depending on the CD4+ T cell count (> or < 500/mm3). Clinical and virological data (including very low‐level viraemia) were collected. In parallel, immunophenotyping of CD4+ lymphocytes, including Treg subsets, and CD8+ T cells was performed. Percentages of activated CD4+ T cells, Tregs, effector Tregs and terminal effector Tregs were found to be significantly elevated in iIR. Neither the percentage of activated CD8+ T cells nor VLLV were found to be associated with iIR. In the multivariate analysis, nadir of CD4+ T cell count and percentage of Tregs were the only two parameters associated independently with iIR [odds ratio (OR) = 2·339, P = 0·001, and OR = 0·803, P = 0·041]. We present here the largest study investigating simultaneously the immune response to long‐term HAART, activation of CD4+ and CD8+ T cells, Treg percentages and very low‐level viraemia. Causative interactions between Tregs and CD4+ T cells should now be explored prospectively in a large patients cohort.